Delineating functional properties of a cello-oligosaccharide and β-glucan specific cellobiohydrolase (GH5_38): Its synergism with Cel6A and Cel7A for β-(1, 3)-(1, 4)-glucan degradation. (September 2020) - Mafa, Mpho S.; Malgas, Samkelo; Rashamuse, Konanani; Pletschke, Brett I.
Abstract: Cellulase cocktails formulated to degrade crystalline cellulose generally contain cellobiohydrolases (CBHs), referred to as CBHI (Cel7A) and CBHII (Cel6A), as the major constituents. The combined hydrolytic activities of CBHI and CBHII improve the release of fermentable sugars (β-1, 4-cellobiose as the main product) from crystalline cellulose. In this study, a novel cellobiohydrolase (Exg-D) sourced from a metagenome of hindgut bacterial symbionts of a termite was heterologouly expressed, purified, and functionally characterised. Exg-D specific activity was higher on insoluble barley β-glucan (38.94 U/mg protein), soluble wheat flour β-glucan (12.71 U/mg protein) and oat β-glucan (8.89 U/mg protein) compared to cellulosic substrates; Avicel and CMC. We further explored Exg-D activity on the unpretreated or NaOH-pretreated (mercerised) Avicel and compared its activity to commercially available CBHI and CBHII on these celluloses. CBHI displayed the highest activity of 4.74 U/mg protein on mercerised cellulose followed by CBHII (2.14 U/mg protein), while Exg-D activity on untreated and mercerised cellulose was 1.66 and 1.67 U/mg protein, respectively. The high activity of CBHI was supported by binding assays, which revealed that CBHI has a higher binding capacity towards crystalline cellulose compared to Exg-D and CBHII. Only CBHI and CBHII showed synergism during the hydrolysis of mercerised Avicel, showing a degree of synergy (DS) of about 1.299 and yielded about 1.43 μmol/ml of reducing sugars higher than control. In contrast, Exg-D and CBHII displayed synergism during β-glucan degradation, displaying a DS of about 1.22. Thus, we propose that Exg-D should only be used synergistically with other CBHs to degrade mixed linked-β-(1, 3)-(1, 4)-glucan. Graphical abstract: Image 1 Highlights: Both Exg-D and CBHII have low binding and activity towards Avicel compared to CBHI. Exg-D and CBHII displayed the highest activity on β-glucan. Exg-D displayed regular cellobiohydrolase activity on cello-oligomers. Exg-D acted anti-synergistically with CBHI during cellulose degradation. Exg-D acted synergistically with CBHII during β-glucan degradation.